Model Pengembangan Pariwisata Berbasis Digital dan Storynomics di Desa Wisata Kamasan - Ni Nyoman Suwaniti; Ni Kadek Riza Indira Kezhya Nanda; Dewa Ayu Sriadi Mastuti; Ni Nyoman Riris Lindya Andini; Ni Made Ayu Natih Widhiarini; Ni Luh Putu Intan Nirmalasari (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2026)
This study explores the development of digital and storynomic-based tourism in Kamasan Tourism Village, Klungkung Regency, Bali. Kamasan is historically known as the center of classical Balinese wayang painting and traditional metal crafts such as gold, silver, and brass. Using a qualitative descriptive method through observation, interviews, and document studies, this research identifies the village’s cultural potential and formulates a sustainable tourism development model. The SWOT analysis reveals that Kamasan’s main strengths lie in its rich cultural heritage, community participation, and diverse local crafts, while weaknesses include limited digital promotion, lack of facilities, and low involvement of younger generations. Opportunities arise from the growing trend of cultural and educational tourism and strong government support for digitalization through the Anugerah Desa Wisata Indonesia (ADWI) program. The integration of storynomic tourism and digital media—such as e-brochures, promotional videos, and virtual tours can enhance destination competitiveness, strengthen local identity, and improve community welfare. This research emphasizes that combining cultural storytelling with digital innovation is a strategic approach to creating sustainable and engaging tourism experiences in Kamasan Village.